Caracterização estrutural e atividades farmacológicas do alginato obtido da alga Dictyopteris delicatula (J.V. Lamouroux., 1809) e seu derivado sulfatado - Florentin, Kahena de Quevedo (2015)
Alginate is a linear polymer compound of D-mannuronic acid(M) linked (1 → 4) at its epimer in C-5 of L-guluronic acid (G). An alginate was isolated and partially purified from brown seaweed D. delicatula (DYN). DYN was chemically sufated (DYS). DYS showed 22% of sulfation and the rate of total sugars was around 66 and 59% for DYN and DYS respectively. DYN DYS and showed a ratio M G of 0.86 and 1.1, respectively. IR signals at 1221cm-1 confirmed the sulfation of DYS. DYN presented anticoagulant activity about intrinsic coagulation pathway, while DYS did not alter the clotting times for aPTT and PT. DYN and DYS also showed antioxidant properties especially ferric chelation where DYN reached about 97% and the OH sequestration where both averaged 85%. In 3T3 cells, DYN indicated proliferation in 24h and 48h of incubation and no cytotoxicity. For tumor lines HeLa and b16, and DYN and DYS decreased significantly the cell viability, especially after 48 hours (about 71% of inhibition). Given the results obtained in this study, it is clear that the sulfation is not decisive for the activity of D. delicatula alginate. In general, DYS and DYN shown as potential compounds to be used pharmacologically, and also in the food industry for revealing be great antioxidant.